Chromosomal instability and acquired drug resistance in multiple myeloma - Wang, Wang (Oncotarget, 2017)
Chromosomal instability (CIN) is an important hallmark of human cancer. CIN not only contributes to all stages of tumor development (initiation, promotion and progression) but also drives, in large measure, the acquisition of drug resistance by cancer cells. Although CIN is a cornerstone of the complex mutational architecture that underlies neoplastic cell development and tumor heterogeneity and has been tightly associated with treatment responses and survival of cancer patients, it may be one of the least understood features of the malignant phenotype in terms of genetic pathways and molecular mechanisms. Here we review new insights into the type of CIN seen in multiple myeloma (MM), a blood cancer of terminally differentiated, immunoglobulin-producing B-lymphocytes called plasma cells that remains incurable in the great majority of cases. We will consider bona fide myeloma CIN genes, methods for measuring CIN in myeloma cells, and novel approaches to CIN-targeted treatments of patients with myeloma. The new findings generate optimism that enhanced understanding of CIN will lead to the design and testing of new therapeutic strategies to overcome drug resistance in MM in the not-so-distant future.